Volatile Flavor Compounds of Pugionium cornutum (L.) Gaertn. Before and After Different Dehydration Treatments - Li, Haoyu; Wu, Qian; Liu, Qiannan; Jin, Lihua; Chen, Bang; Li, Cong; Xiao, Jianbo; Shen, Yehua (Frontiers in Nutrition, 2022)
Pugionium cornutum (L.) Gaertn (also Pugionium) is a special Mongolian vegetable, belonging to the Cruciferous family, growing in arid and semi-arid areas of northern China, with a unique flavor and potential health benefits. This paper aims to describe the profile of volatile flavor compounds in fresh and different dehydrated samples, establish the fingerprint and identify the characteristic compounds. The fresh Pugionium sample and 3 kinds of dehydrated samples were analyzed. Headspace/Gas Chromatography-Ion Migration Spectrometry (HS/GC-IMS) and Solid-phase microextraction/Gas Chromatography-Mass Spectrometry (SPME/GC-MS) were used for identification and relative quantification. HS/GC-IMS identified 78 compounds, whereas SPME/GC-MS identified 53 compounds. Principal component analysis (PCA), clustering analysis, and partial least squares discriminant analysis (PLS-DA) were used as appropriate to investigate variations in volatile compounds among Pugionium samples and identify distinctive compounds. The first two principal components described 76.5 % and 69.5 % of the variance of the data from HS/GC-IMS and SPME/GC-MS, respectively. By clustering analysis, 4 kinds of Pugionium samples could be classified into four independent groups. The similarity between fresh Pugionium and natural dehydration Pugionium was higher than the other two dehydrated samples, indicating that natural dehydration can better preserve the flavor of Pugionium. Most aldehydes and alcohols increased following different dehydration procedures, whereas esters dropped, and the dehydrated Pugionium samples have a more harmonious and less pungent aroma than the fresh. PLS-DA model analysis revealed that the characteristic compound (VIP scores > 1) discriminating flavor of the four samples for HS/GC-IMS and SPME/GC-MS were 24 and 15 compounds, respectively, such as 2-phenylethyl isothiocyanate, 1-butene-4-isothiocyanate and other isothiocyanates, 2-propanone, nonanal, gamma-butyrolactone, 2,3-butanediol, 3-methyl-2-butenenitrile, and pentanal, etc. Analysis of volatile compounds might be useful for monitoring the quality of Pugionium and guiding the cooking methods and processing technologies. More study is required to discover if the various volatile flavor compounds have biological or physiological impacts on nutrition.